Teaching and Learning Indicators in University Rankings - Essack, Sabiha; Naidoo, Indirani (South African Journal of Higher Education, 2016)
Quality teaching and learning is critical to producing high caliber University graduates equipped with the knowledge, skills and values to contribute to the knowledge economy and the economic growth and development of countries while ensuring self-efficacy and personal success. Teaching quality measures and indicators have, however, not enjoyed adequate debate and discourse within the higher education sector, and, as such are largely quantitative and measured by proxy in University ranking systems. Proxy teaching indicators used by the Quacquarelli Symonds (QS) World University Rankings and the Times Higher Education (THE) World University Rankings were correlated with U-Multirank indicators applicable to the Faculty of Health Sciences for the period 2007-2011, with the Faculty considered as a microcosm of the University of KwaZulu-Natal. There were no statistically significant differences in the indicators between years. There were just 2 significant correlations, viz., ratio of PhD to Bachelors degrees awarded significantly correlated with throughput from cohort at 95% and 99% while the number of PhDs significantly correlated with graduate employment at 90%. Teaching quality measurement by proxy is thus justifiably contested in University rankings. The challenge for University ranking systems is thus (1) identifying suitable quantitative and qualitative indicators for quality teaching, (2) striking the correct balance between quantitative and qualitative teaching quality indicators, and (3), ensuring that the quantitative/ qualitative indicators address both teaching inputs and teaching impact/learning outcomes.